Eco-friendly polymers based on Baru vegetable oil and fumaric acid using photopolymerization - Magri, Raquel [UNESP]; Gaglieri, Caroline [UNESP]; Alarcon, Rafael Turra; dos Santos, Gabriel Iago [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2023)
Biomass-derivative materials are one of the answers to substitute materials from finite sources in the coming decades. Thus, the present paper demonstrates the syntheses of new polymers based on epoxidized Baru oil and fumaric acid by photopolymerization, which were investigated by incorporating different proportions of urethane dimethacrylate using ultraviolet and blue lights. The monomers and polymers were characterized by spectroscopic, thermal, and mechanical analyses. The incorporation of acrylate derivatives into the monomeric mixture increases the reactivity of monomers, achieving conversions >98% in both irradiation sources. Besides all polymeric materials presented thermal stability above 200 °C, they were transparent films that were able to remove some dyes from water, resulting in luminescent materials. In addition, the degradation processes of these polymers can be accelerated by organic solvents. Based on these properties, it is suggested that these eco-friendly polymeric materials can be used as coating, due to their partial transparency, and also for application in colored polymeric matrices, as well as dye remover in aqueous systems.
Keywords: Dimethacrylate monomers; Dipteryx alata Vogel; Fumaric acid; Renewable monomer